Follicular Bronchiolitis in a Nigerian Female Child: A Case Report and Review of the Literature - Ikeri, Nzechukwu Zimudo (Case Rep Pediatr, 2016)
Small airways diseases are not uncommon in childhood. They account for about 28.4% of hospital admissions for lower respiratory tract infections in South West Nigeria, most of which are due to respiratory syncytial virus (RSV) infection. Noninfectious causes of small airways diseases, on the other hand, are poorly recognized and rarely feature in the differential diagnoses of chronic/recurrent lower respiratory tract disease in our environment. We present a case of follicular bronchiolitis in a 2.5-year-old Nigerian female who had left upper lobectomy on account of recurrent cough and progressive shortness of breath.